2019
DOI: 10.1074/jbc.ra119.007967
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor NKX1-2 promotes adipogenesis and may contribute to a balance between adipocyte and osteoblast differentiation

Abstract: Although adipogenesis is mainly controlled by a small number of master transcription factors, including CCAAT/enhancer-binding protein family members and peroxisome proliferator-activated receptor ␥ (PPAR␥), other transcription factors also are involved in this process. Thyroid cancer cells expressing a paired box 8 (PAX8)-PPAR␥ fusion oncogene trans-differentiate into adipocyte-like cells in the presence of the PPAR␥ ligand pioglitazone, but this trans-differentiation is inhibited by the transcription factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…As shown on Figure 1 D, the expression of all the 50 genes identified was dramatically reduced in the LPM/ST hLECs group. Amongst them, several are known to encode proteins that regulate particularly important epithelial cell functions such as apoptosis ( ST18 , CISD3 ) [ 39 , 40 ], differentiation ( TBR1 , BARX1 , NKX1-2 , FOXB1 , APOL1 , PROP1 , TSACC ) [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], proliferation ( CEBPD , MNX1-AS1 , GPR75 , FZD9 , GAS2L3 , PFKL , TPT1-AS1 , CYP17A1 , MIR22HG ) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], and migration ( ARHGAP9 , ITGAM , EMILIN1 , ZNF554 , SOX8 ) [ 59 , 60 , 61 , 62 , 63 ]. Moreover, the involvement of some of these genes in the cellular functions listed above was validated further by our IPA analyses.…”
Section: Resultsmentioning
confidence: 99%
“…As shown on Figure 1 D, the expression of all the 50 genes identified was dramatically reduced in the LPM/ST hLECs group. Amongst them, several are known to encode proteins that regulate particularly important epithelial cell functions such as apoptosis ( ST18 , CISD3 ) [ 39 , 40 ], differentiation ( TBR1 , BARX1 , NKX1-2 , FOXB1 , APOL1 , PROP1 , TSACC ) [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], proliferation ( CEBPD , MNX1-AS1 , GPR75 , FZD9 , GAS2L3 , PFKL , TPT1-AS1 , CYP17A1 , MIR22HG ) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], and migration ( ARHGAP9 , ITGAM , EMILIN1 , ZNF554 , SOX8 ) [ 59 , 60 , 61 , 62 , 63 ]. Moreover, the involvement of some of these genes in the cellular functions listed above was validated further by our IPA analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The regulation of adipocyte differentiation by Nkx1‐2 is a complex process that involves multiple signaling pathways and transcriptional interactions. According to the model proposed by Chen et al, Nkx1‐2 represses expression of COUP transcription factor 2, which otherwise represses PPARγ and C/EBPα [20]. By repressing COUP transcription factor 2, Nkx1‐2 indirectly promotes the expression of PPARγ and C/EBPα, thereby facilitating adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Chen et al have shown that Nkx1‐2 may regulate the balance between adipocyte and osteoblast differentiation of ST2 cells (bone marrow‐derived stromal cell) [20]. This suggests a potential role for Nkx1‐2 in adipogenesis, but further in vivo evidence is required to confirm this conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…NKX1-2: NK1 homeobox 2, a TF that belongs to the NKX family of proteins, is shown to be induced during 3T3L-1 adipocyte differentiation [ 137 ]. Additionally, shRNA-mediated knockdown of NKX1-2 in 3T3L-1 cells or in-ear MSCs wholly abrogated adipocyte differentiation.…”
Section: Transcriptional Factors Of White Adipocytes and Browningmentioning
confidence: 99%